The Conflict of Laws Rules on Contractual Obligations in the Federal state: A Comparative Study with U.S. Second Restatement - Ali, Younis Salahuddin (Journal of Legal and Political Studies, 2025)
This research is concerned with studying the scope of the application of the conflict of laws rules on the contractual obligations in the interstate conflict of laws in the federal state. The article adopts the U.S. law as a paradigm, in conformity with the U.S. second restatement of the conflict of laws, compared with the situation of the current conflict of laws rules in the Iraqi civil law No. (40) of 1951. The U.S. second restatement can solve the interstate conflict of laws on the contractual obligations, by both the article 187 and 188. It encompasses the solution of the interstate conflict of laws in the case of the choice of law. And in the case of the determination of the applicable state law in the absence of the choice of law by the contracting parties. The problem of the research lies in the shortage and insufficiency of the situation of the conflict of laws rules in the Iraqi civil law No. (40) of 1951, concerning the inter-territorial (inter-regional) conflict of laws. This study has adopted to the analytical comparative methodology of the legal research, and the main finding of this study is that the first paragraph of the article (25) is not concerned with solving the inter-territorial conflict of laws in the federal state. The researcher suggests some relevant recommendations to the Iraqi legislator, the most important of which is to suggest a legal regulation for solving the inter-regional conflict of laws in the federal Iraq. Keywords: Chosen Law, Second Restatement, The Conflict of Laws Rules, Interstate Conflict of Laws, Connecting Factors.
Keywords: Chosen Law; Second Restatement; The Conflict of Laws Rules; Interstate Conflict of Laws; Connecting Factors